FREQUENCY OF HEARING LOSS AND OTITIS MEDIA IN CHILDREN WITH ADENOID HYPERTROPHY - Khan, Imran; Bibi, Anila (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the frequency of hearing loss and otitis media with effusion in patients with adenoid hypertrophy. Methodology: An observational study was performed in the Department of Pediatrics, Children Hospital/Institute of Child health, Lahore, from January 20, 2016 to July 19, 2016. A total of 100 patients with adenoid hypertrophy and 1-16 years of age were included in the study. Frequency of hearing loss and otitis media with effusion were determined. Data was collected on pre designed profarma and analyzed using SPSS version 20. Results: Mean age of the patients was 7.32 ±3.26 years. Majority of the patients were aged between 5-8 years (60%). There were 64 (64%) males in the study. The duration of adenoid hypertrophy ranged from 4 months to 12 months with a mean of 7.90 ±2.51 months. Otitis media with effusion (OME) was detected in 74 (74%) patients. It increased significantly with increasing duration of adenoid hypertrophy; 4-6 months vs. 7-9 months vs. 10-12 months (56.3% vs. 72.2% vs. 93.8%; p=0.003). Hearing loss was observed in 56 (56.0%) patients. The frequency of hearing loss increased with increasing duration of adenoid hypertrophy; 4-6 months vs. 7-9 months vs. 10-12 months (12.5% vs. 27.8% vs. 37.5%; p=0.248), however, the difference was statistically insignificant. Conclusion: Increased frequency of otitis media with effusion and hearing loss was found in patients suffering from adenoid hypertrophy. Frequency of otitis media with effusion increased significantly with increasing duration of adenoid hypertrophy.